PROFESIONALISME GURU TPQ BAITUL JANNAH - Donny Khoerul Aziz (IAIN Purwokerto, 2015)
Abstract: The results of this study showed that increasing the professionalism of TPQ's teachers more focused on coaching and training in order to realize professional teachers. Efforts to develop the professionalism of teachers can arise from two aspects, namely: (1) from the extemal side, the leaders who encourage teachers to take upgrading courses or academic activities, or their educational institutions that provide opportunities for teachers to leam more; and (2) in temms of intemal, namely the desire of an educator to acquire and improve its capabilities. And this factor is the most important and decisive factor. Efforts to improve the professionalism of TPQ's teachers become a crucial aspect in the leaming process, because the success is in the hands of teachers. In improving the professionalism of TPQ's teachers there are some things that can be done namely tartil Quran courses, upgrading and management courses, and TPQ unit coaching. Keywords: Professionalism, TPQ's Teacher.